The effect of fancy rope jumping exercise on creativity of elementary school students - Chao Wang; Xiaoxiao Zhang; Hansen Li; Guodong Zhang (Nicolaus Copernicus University in Toruń, 2022)
Purpose: To explore the effects of 6 months of moderate intensity fancy rope jumping exercise on the creativity of elementary school students. Methodology: One hundred and forty elementary school students were divided into two major groups, namely, the fancy rope jumping group and the traditional sports group. The Williams Creative Tendency Scale (WCTS) and Torrance Creative Thinking Scale (TTCT) were used to measure the changes of creative tendency and divergent thinking of elementary school students before and after the experiment, and to compare to evaluate the change of creativity of elementary school students by measuring the difference between the experimental group and the control group. Findings: (1) Six months of moderate intensity fancy rope jumping exercise had a positive effect on elementary school students' creative tendencies and divergent thinking; (2) Six months of moderate fancy rope jumping exercise had a more significant effect on elementary school students' divergent thinking. Research and practical limitations/implications: This study confirms experimentally that fancy rope jumping helps to enhance the creative tendency and divergent thinking level of elementary school students and promotes the development of their creativity. The limitation of this study is that the sample size is relatively small and not representative and convincing enough. In the follow-up study, we can make the research results more convincing by expanding the research sample size and sampling across regions.